PENERAPAN TEKNIK LEKSIKOSTATISTIK DALAM STUDI KOMPARATIF BAHASA BARANUSA, KEDANG, DAN LAMAHOLOT DI NUSA TENGGARA TIMUR - Yunus Sulistyono; Inyo Yos Fernandez (Jurnal Penelitian Humaniora, 2015)
Alor-Pantar islands lie between Austronesian and non-Austronesian languages. Baranusa, one of the Austronesian languages spoken in the island of Pantar, estimated to have a kinship relation with Kedang and Lamaholot, two other Austronesian languages spoken in Lembata and East Flores. This hypothesis arises from a glance observation of base form of the three languages. The method of the current study is a quantitative method with lexicostatistics technique. The data were 200 base forms of Swadesh taken from three languages, namely Baranusa, Kedang, and Lamaholot. The data were analyzed quantitatively to find out the percentage of kinship and arranged in the form of a family tree diagram.  The result leads to the conclusion that Baranusa, Kedang, and Lamaholot have a close kinship relations.